Preparation method and application of potassium-doped iron-manganese-based positive electrode material

Through the regulation of K+ doping and manganese vacancy content, combined with the optimization of cooling speed, the problem of structural instability of Fe/Mn-based cathode material under high pressure is solved, achieving efficient and stable sodium ion transmission and extended battery life.

CN119560555APending Publication Date: 2025-03-04NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411658686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The Fe/Mn-based cathode material has a sharp attenuation of capacity due to high-pressure oxygen loss in high-pressure crystal lattice and unstable crystal structure under high-pressure, which limits its application in sodium ion batteries.

Method used

Through precise regulation of K+ doping and manganese vacancy content, combined with the regulation of cooling speed, a stable potassium-doped iron-manganese-based cathode material is constructed to optimize its crystal structure and sodium ion transport efficiency.

Benefits of technology

It improves the crystal structure stability and sodium ion transmission efficiency of the positive electrode material, extends the battery life, and achieves efficient and stable sodium storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560555A_ABST
    Figure CN119560555A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a potassium-doped ferro-manganese-based positive electrode material, and belongs to the technical field of electrochemical energy storage. The preparation method comprises the following steps: mixing weighed raw materials according to the molar ratio of metal elements, carrying out ball milling, tabletting, carrying out high-temperature calcination, and then regulating and controlling the cooling speed to realize fine regulation and control on a manganese vacancy; the chemical general formula of the potassium-doped iron-manganese-based positive electrode material is Na < 0.67 > KsMn < 0.5-0.8 > Fe < 0.5-0.2 > O < 2 >, the relationship between the content of the manganese vacancy and the cooling speed is Y = 0.15623 + 0.04976 e-x / 19.18786, x represents the cooling speed, and Y represents the content of the manganese vacancy. Fine regulation and control of manganese vacancy are realized by regulating and controlling the cooling speed, on one hand, the crystal structure stability of the positive electrode material can be improved, and on the other hand, efficient transmission of sodium ions can be promoted; according to the invention, doping modification, defect engineering and electrochemical performance are ingeniously combined together, the preparation process is simple, the cost is low, and the method is suitable for large-scale commercial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a preparation method and application of a potassium-doped iron-manganese-based positive electrode material. Background Art

[0002] At present, energy consumption mainly comes from fossil fuels. With the development of human society and the rapid growth of industry, the loss of fossil fuels is also increasing sharply. Excessive consumption will cause energy depletion and trigger a series of environmental problems, such as greenhouse effect, acid rain and industrial pollution. In the face of these energy and environmental problems, the development of environmentally friendly, clean, safe and stable energy storage technology is a scientific problem that researchers are currently urgently trying to solve. Sodium-ion batteries are a promising new energy storage technology because of their wide distribution, high reserves and low cost. Therefore, the development of related sodium-ion batteries with high capacity, high energy density and long life has become a top priority. New energy storage cathode materials are the key to maintaining the high capacity, high energy and long life of sodium-ion batteries.

[0003] Fe / Mn-based cathode materials have relatively excellent capacity (190 mAh g -1 ), low price, and easy preparation have attracted great attention, and many researchers have tried to apply it to the field of sodium-ion battery energy storage. However, its high-voltage harmful phase change causes its capacity to decay sharply, threatening its battery life cycle, resulting in its application in electrochemical energy storage being greatly limited. It is reported that potassium ion doping can inhibit high-voltage lattice oxygen loss and optimize the stability of the crystal structure, which is expected to achieve efficient and stable sodium storage. However, there is currently a lack of relevant systematic reports on potassium ion doping in Fe / Mn-based positive electrode material systems. In particular, the pillar effect of Na-site potassium ion doping on the stabilization effect of the Fe / Mn-based positive electrode crystal structure under high voltage is still unknown.

[0004] At the same time, the cooling rate during the synthesis process is of great significance for obtaining materials with stable structure and excellent performance, and the impact is more obvious for manganese-based oxides. 0.67 During the slow cooling process, Na 0.67 MnO2 can absorb oxygen, leading to the increase of the oxidation state of Mn ions and the formation of manganese defect phases. 3+ Will spontaneously ask Mn 4+ This study shows that Mn vacancies are easily formed in the transition metal layer during the cooling process, and excessive Mn vacancies will bind the adjacent Na + , which is not conducive to the transport of sodium ions. However, this mechanism is still lacking in Fe / Mn-based cathode materials, and there is no systematic formula to explain the evolution law between cooling rate and manganese vacancy content. +The synergistic effect of doping and manganese vacancy design engineering for high-performance Na-ion storage is of great strategic significance. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a preparation method and application of potassium-doped iron-manganese-based positive electrode materials. The present invention achieves fine control of manganese vacancies by regulating the cooling rate, which can improve the crystal structure stability of the positive electrode material on the one hand, and promote the efficient transmission of sodium ions on the other hand; the present invention cleverly combines doping modification, defect engineering and electrochemical performance, has a simple preparation process, low cost, and is suitable for large-scale commercial production.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a potassium-doped iron-manganese-based positive electrode material, the preparation method comprising: + The iron-manganese-based positive electrode material is obtained by dual optimization modification of doping and precise control of manganese vacancy content. The preparation method comprises the following steps:

[0008] (1) mixing the weighed raw materials according to the molar ratio of metal elements and ball milling;

[0009] (2) pressing the sample obtained after ball milling into a tablet and calcining it at high temperature;

[0010] (3) cooling the material after high-temperature calcination, and adjusting the cooling rate to achieve fine adjustment of manganese vacancies, thereby obtaining the potassium-doped iron-manganese-based positive electrode material;

[0011] The general chemical formula of the potassium-doped iron-manganese-based positive electrode material is: Na 0.67 K s Mn 0.5-0.8 Fe 0.5-0.2 O2, where K doping is located at the Na site;

[0012] The relationship between the manganese vacancy content and the cooling rate is: Y = 0.15623 + 0.04976e -x / 19.18786 , where x represents the cooling rate and Y represents the manganese vacancy content.

[0013] Preferably, the doping amount of K is s=0-0.02.

[0014] Preferably, in the raw materials of step (1), the sodium source is sodium carbonate, the manganese source is manganese oxide, the iron source is iron oxide, and the potassium source is potassium carbonate.

[0015] Furthermore, the relative molar content of sodium carbonate in the raw material of step (1) (5% excess) avoids sodium loss during the high temperature calcination process;

[0016] Preferably, the ball milling process in step (1) uses anhydrous ethanol as the medium and the ball milling time is 6-12 hours.

[0017] Preferably, the high temperature calcination process conditions in step (2) are as follows: the calcination atmosphere is air, the calcination temperature is 800-1000°C, the time is 8-16h, and the heating rate is 5-10°C / min.

[0018] Furthermore, the calcination temperature of step (2) converts the positive electrode material into a P2 phase structure. If the temperature is too low, the reaction does not start or is incomplete, resulting in an impurity phase (such as a P3 phase). If the temperature is too high, it may cause unnecessary power loss on the one hand, and on the other hand, it may cause excessive crystal growth. The same is true for the calcination time. If the calcination time is too short, the reaction does not start or is incomplete, and the grains do not grow by charge and discharge. If the calcination time is too long, the grains grow excessively and cause agglomeration, which is not conducive to ion / charge transport.

[0019] Preferably, the method for regulating the cooling rate in step (3) is: using a constant temperature drying oven, setting the temperature to 40-80°C, and performing constant temperature cooling, thereby obtaining a cooling rate of 15-80°C / min.

[0020] Furthermore, in the method for regulating the cooling rate in step (3), if the temperature of the constant temperature drying oven is set to 40°C and constant temperature cooling is performed at this temperature, the cooling rate is about 80°C / min.

[0021] The present invention also provides an application of the potassium-doped iron-manganese-based positive electrode material obtained by the preparation method, and the potassium-doped iron-manganese-based positive electrode material is used in a sodium ion battery to achieve efficient and stable sodium storage.

[0022] The beneficial technical effects of the present invention are:

[0023] 1. The present invention is different from the conventional method of Fe / Mn-based positive electrode modification in the prior art. It controls the cooling rate to construct manganese vacancies of different contents, thereby improving the sodium ion transmission efficiency and improving its electrochemical performance. More importantly, the present invention establishes a functional relationship between cooling rate and manganese vacancy content to reasonably evaluate the evolution law of manganese vacancy content.

[0024] 2. The present invention adopts Na-K + Doping optimization modification can eliminate high-voltage lattice oxygen loss, improve crystal structure stability, and have a proper improvement effect on electrical properties.

[0025] 3. The present invention skillfully combines Fe / Mn-based positive electrode, defect engineering, doping modification and electrochemistry, and has great application potential. The present invention has a high reproducibility, a simple preparation process, and is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the Fe / Mn-based positive electrode material prepared in Example 1;

[0027] Figure 2 0.1C first cycle charge-discharge curve of the Fe / Mn-based positive electrode material prepared in Example 1-5;

[0028] Figure 3 Cooling rate-manganese vacancy content analysis of the Fe / Mn-based positive electrode materials prepared in Examples 1-5;

[0029] Figure 4 EIS analysis of the Fe / Mn-based cathode materials prepared in Examples 1-5;

[0030] Figure 5 0.1C cycle performance test of the Fe / Mn-based cathode materials prepared in Examples 1 and 5;

[0031] Figure 6 Median voltage test of the Fe / Mn-based positive electrode materials prepared in Examples 1 and 5. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] If there is no special description of raw materials or processing techniques, it means that they are all conventional commercially available raw materials or conventional processing techniques in the field.

[0034] Embodiment 1:

[0035] (1) The chemical formula of the positive electrode material prepared in this embodiment is Na 0.67 K 0.01 Mn 0.5 Fe 0.5 O2, weighed according to the metal element molar ratio n(Na):n(K):n(Mn):n(Fe)=0.67:0.01:0.5:0.5, using ethanol as the medium, sodium carbonate as the sodium source (5% excess, 1.855 mg), manganese oxide as the manganese source (1.973 mg), iron oxide as the iron source (1.996 mg), potassium carbonate as the potassium source (0.035 mg), ball milled for 6 hours, and fully mixed;

[0036] (2) The ball-milled sample was calcined at a high temperature in an air atmosphere, wherein the calcination temperature was 900°C, the time was 12 h, and the heating rate was 5°C / min;

[0037] (3) The calcined sample is directly placed in a 40°C constant temperature drying oven at a cooling rate of about 80°C / min until it cools to room temperature to obtain a sample.

[0038] (4) Substitute the above obtained K + The doped and rapidly cooled (80°C / min) Fe / Mn-based positive electrode material was cut into 10 mm pole pieces, the loading amount was controlled at 1.0-1.3 mg, and assembled into a half-cell. 1.0 M NaClO4 + PC / EC (1:1) + 5% FEC was used as the electrolyte, and the half-cell system was selected to measure its electrochemical properties.

[0039] The SEM image of the potassium-doped iron-manganese-based positive electrode material prepared in this example is as follows: Figure 1 As shown in the figure, it can be seen that the sample prepared in Example 1 is an irregular flaky structure with a relatively uniform grain distribution, which avoids the occurrence of agglomeration. This shows that the dual modification strategy is conducive to the formation of fine and uniform particles and increases the specific surface area of ​​the positive electrode material.

[0040] Embodiment 2:

[0041] (1) The chemical formula of the positive electrode material prepared in this embodiment is Na 0.67 K 0.01 Mn 0.5 Fe 0.5 O2, weighed according to the metal element molar ratio n(Na):n(K):n(Mn):n(Fe)=0.67:0.01:0.5:0.5, using ethanol as the medium, sodium carbonate as the sodium source (5% excess, 1.855 mg), manganese oxide as the manganese source (1.973 mg), iron oxide as the iron source (1.996 mg), potassium carbonate as the potassium source (0.035 mg), ball milled for 6 hours, and fully mixed;

[0042] (2) The ball-milled sample was calcined at a high temperature in an air atmosphere, wherein the calcination temperature was 900°C, the time was 12 h, and the heating rate was 5°C / min;

[0043] (3) The calcined sample is directly placed in a 60°C constant temperature drying oven at a cooling rate of about 40°C / min until it cools to room temperature to obtain a sample.

[0044] (4) Substitute the above obtained K + The doped and moderately cooled (40°C / min) Fe / Mn-based cathode materials were assembled into flexible half-cells, and the specific method was the same as in Example 1.

[0045] Embodiment 3:

[0046] (1) The chemical formula of the positive electrode material prepared in this embodiment is Na 0.67 K 0.01 Mn0.5 Fe 0.5 O2, weighed according to the metal element molar ratio n(Na):n(K):n(Mn):n(Fe)=0.67:0.01:0.5:0.5, using ethanol as the medium, sodium carbonate as the sodium source (5% excess, 1.855 mg), manganese oxide as the manganese source (1.973 mg), iron oxide as the iron source (1.996 mg), potassium carbonate as the potassium source (0.035 mg), ball milled for 6 hours, and fully mixed;

[0047] (2) The ball-milled sample was calcined at a high temperature in an air atmosphere, wherein the calcination temperature was 900°C, the time was 12 h, and the heating rate was 5°C / min;

[0048] (3) The calcined sample is directly placed in a constant temperature drying oven at 80°C. At this time, it is determined that the cooling rate is about 15°C / min until it cools to room temperature to obtain the sample.

[0049] (4) Substitute the above obtained K + The doped and slowly cooled (15°C / min) Fe / Mn-based cathode material was assembled into a flexible half-cell, and the specific method was the same as in Example 1.

[0050] Embodiment 4:

[0051] (1) The chemical formula of the positive electrode material prepared in this embodiment is Na 0.67 K 0.02 Mn 0.5 Fe 0.5 O2, weighed according to the metal element molar ratio n(Na):n(K):n(Mn):n(Fe)=0.67:0.02:0.5:0.5, using ethanol as the medium, sodium carbonate as the sodium source (5% excess, 1.855 mg), manganese oxide as the manganese source (1.973 mg), iron oxide as the iron source (1.996 mg), potassium carbonate as the potassium source (0.069 mg), ball milled for 12 hours, and fully mixed;

[0052] (2) The ball-milled sample was calcined at high temperature in an air atmosphere, wherein the calcination temperature was 800°C, the time was 8 h, and the heating rate was 10°C / min;

[0053] (3) The calcined sample is directly placed in a 40°C constant temperature drying oven at a cooling rate of about 80°C / min until it cools to room temperature to obtain a sample.

[0054] (4) Substitute the above obtained K + The doped and rapidly cooled (80°C / min) Fe / Mn-based cathode material was assembled into a flexible half-cell, and the specific method was the same as in Example 1.

[0055] Embodiment 5:

[0056] (1) The chemical formula of the positive electrode material prepared in this embodiment is Na 0.67 Mn 0.5 Fe 0.5 O2, weighed according to the metal element molar ratio n(Na):n(Mn):n(Fe)=0.67:0.5:0.5, using ethanol as the medium, sodium carbonate as the sodium source (5% excess, 1.855 mg), manganese oxide as the manganese source (1.973 mg), and iron oxide as the iron source (1.996 mg), ball milled for 6 hours and mixed thoroughly;

[0057] (2) The ball-milled sample was calcined at a high temperature in an air atmosphere, wherein the calcination temperature was 1000°C, the time was 16 h, and the heating rate was 10°C / min;

[0058] (3) The calcined sample is directly placed in a 40°C constant temperature drying oven at a cooling rate of about 80°C / min until it cools to room temperature to obtain a sample.

[0059] (4) The above-mentioned rapidly cooled (80°C / min) Fe / Mn-based positive electrode material is assembled into a flexible half-cell, and the specific method is the same as that in Example 1.

[0060] Test example:

[0061] Manganese vacancy design engineering assisted the electrochemical performance test of iron-manganese based cathode materials:

[0062] Using a blue light and electrochemical workstation, 1.0 M NaClO4 + PC / EC (1:1) + 5% FEC was used as the electrolyte, and a half-cell was assembled to measure its electrochemical properties, with the sodium electrode as the counter electrode.

[0063] The 0.1C first cycle charge-discharge curve of the Fe / Mn-based cathode material prepared in Example 1-5 is as follows: Figure 2 As shown, the initial discharge capacity of the sample in Example 1 is 199.5 mAh / g, the initial discharge capacity of the sample in Example 2 is 183.3 mAh / g, the initial discharge capacity of the sample in Example 3 is 170.5 mAh / g, the initial discharge capacity of the sample in Example 4 is 152.1 mAh / g, and the initial discharge capacity of the sample in Example 5 is 145.7 mAh / g. + The dual modification of doping can relieve the binding of manganese vacancies and Na + effect, and with the help of K + The doped pillar effect strengthens the sodium ion transmission channel and realizes efficient sodium ion transmission, so the specific capacity performance of the sample is greatly improved.

[0064] The quantitative analysis of the Mn / Fe ratio is shown in Table 1. The manganese vacancy content of the sample in Example 1 is 0.157, the manganese vacancy content of the sample in Example 2 is 0.162, the manganese vacancy content of the sample in Example 3 is 0.179, the manganese vacancy content of the sample in Example 4 is 0.156, and the manganese vacancy content of the sample in Example 5 is 0.158. Figure 3 The cooling rate-manganese vacancy content of the Fe / Mn-based positive electrode material prepared in Example 1-5 is shown in Figure 1. The relationship between the cooling rate and the manganese vacancy content is Y=0.15623+0.04976e -x / 19.18786 (x represents the cooling rate, Y represents the manganese vacancy content), and R 2 is 0.99934. This also shows the rationality of the fitting results.

[0065] Table 1 Quantitative analysis of Mn / Fe ratio

[0066]

[0067]

[0068] Note: The theoretical ratio of Mn / Fe is 1, and the difference indicates the Mn vacancy content.

[0069] The EIS analysis of the Fe / Mn-based cathode materials prepared in Examples 1-5 is as follows: Figure 4 As shown, Example 1 Sample R ct is 325.13Ω, Example 2 Sample R ct is 354.42Ω, and R of the sample in Example 3 ct is 377.29Ω, Example 4 Sample R ct is 378.93Ω, Example 5 Sample R ct The present invention combines the precise control of manganese vacancy content and K + Double modification by doping, optimizing to obtain a small amount of Mn vacancies and K + On the one hand, the presence of a small amount of manganese vacancies will alleviate the Na + On the other hand, K + The stabilizing effect of doping can strengthen the sodium ion transmission channel, thereby accelerating the rapid transmission of sodium ions. ct The smallest, the sodium ion transfer efficiency is the highest.

[0070] The 0.1C cycle performance test of the Fe / Mn-based cathode materials prepared in Examples 1 and 5 is as follows: Figure 5As shown, at 0.1C, the first cycle discharge specific capacities of Example 1 and Example 5 are 192.7mAh / g and 142.8mAh / g, respectively. The discharge specific capacities after 50 cycles are 118.6mAh / g and 70.2mAh / g, respectively, and the capacity retention rates are 61.5% and 49.2%, respectively. Compared with the sample in Example 5, the cycle performance of the sample in Example 1 is improved by about 10%. The main reason is that the pillar effect of K ions at the Na position can quickly insert and remove Na + The Na layer is better supported during the process, thereby stabilizing the crystal structure and ensuring rapid stabilization of the Na + transmission.

[0071] The median voltage test of the Fe / Mn-based positive electrode materials prepared in Examples 1 and 5 is as follows: Figure 6 As shown in the figure, the working voltages of Example 1 and Example 5 both show a tendency to decay as the number of cycles increases. The average working voltage of Example 1 is higher than that of Example 5, and has a better voltage holding rate. The main reason is still that K + The pillar effect stabilizes the crystal structure of the positive electrode material. Therefore, it can be judged that the average working voltage of Example 1 is higher.

[0072] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a potassium-doped iron-manganese-based positive electrode material, characterized in that: The preparation method comprises K + The iron-manganese-based positive electrode material is obtained by dual optimization modification of doping and precise control of manganese vacancy content. The preparation method comprises the following steps: (1) mixing the weighed raw materials according to the molar ratio of metal elements and ball milling; (2) pressing the sample obtained after ball milling into a tablet and calcining it at high temperature; (3) cooling the material after high-temperature calcination, and adjusting the cooling rate to achieve fine adjustment of manganese vacancies, thereby obtaining the potassium-doped iron-manganese-based positive electrode material; The general chemical formula of the potassium-doped iron-manganese-based positive electrode material is: Na 0.67 K s Mn 0.5-0.8 Fe 0.5-0.2 O2, where K doping is located at the Na site; The relationship between the manganese vacancy content and the cooling rate is: Y = 0.15623 + 0.04976e -x / 19.18786 , where x represents the cooling rate and Y represents the manganese vacancy content.

2. The preparation method according to claim 1, characterized in that: The doping amount of K is s=0-0.

02.

3. The preparation method according to claim 1, characterized in that: In the raw materials of step (1), the sodium source is sodium carbonate, the manganese source is manganese oxide, the iron source is iron oxide, and the potassium source is potassium carbonate.

4. The preparation method according to claim 1, characterized in that: The ball milling process described in step (1) uses anhydrous ethanol as the medium and the ball milling time is 6-12 hours.

5. The preparation method according to claim 1, characterized in that: The high temperature calcination process conditions described in step (2) are specifically as follows: the calcination atmosphere is air, the calcination temperature is 800-1000°C, the time is 8-16h, and the heating rate is 5-10°C / min.

6. The preparation method according to claim 1, characterized in that: The method for regulating the cooling rate in step (3) is: using a constant temperature drying oven, setting the temperature to 40-80°C, and performing constant temperature cooling to obtain a cooling rate of 15-80°C / min.

7. Application of the potassium-doped iron-manganese-based positive electrode material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The potassium-doped iron-manganese-based positive electrode material is used in sodium-ion batteries to achieve efficient and stable sodium storage.

Citation Information

Patent Citations

  • Preparation method of high-performance ferromanganese-based Na &lt; 0.67 &gt; TM &lt; x &gt; Mn &lt; 0.9-x &gt; Fe &lt; 0.1 &gt; O &lt; 2-delta &gt; sodium ion battery positive electrode material

    CN116161705A

  • P2 type layered positive electrode material, preparation method thereof, positive plate and sodium ion battery

    CN118507706A